Knowledge and Awareness of usage of Artificial Sweeteners among Indian type 2 diabetes individuals in a tertiary diabetes institute - Sharanya S Shetty, Dietitian; R Anil Kumar; Shruthi R (International Journal of Medical Research and Review, 2022)
Background: Diabetes mellitus is a chronic metabolic disease primarily attributable to unhealthy, untimely food habits and lack of physical activity. Good glycemic control is one of the key aspects in preventing complications. This has led to a shift in replacing sugar with artificial sweeteners amongst the diabetic population. It is not known whether this is aimed to maintain blood glucose levels or to satisfy the sweet cravings. There is lack of awareness of the type and long-term side effects of artificial sweeteners among people with diabetes. Objectives: This study was conducted to assess the awareness and knowledge of usage of artificial sweeteners among adults with type 2 diabetes visiting a tertiary diabetes institute. Materials and Methods: The study population involved 297 adults (≥18 years) with type 2 diabetes attending tertiary diabetes institute. Data was collected from face-to-face interview technique along with a pre-validated questionnaire. Results: The total number of subjects (n=297) comprised 126 females and 171 males of age 18-88 with mean age of 56.5 years. Sucralose was the most popular sugar substitute amongst the subjects (45%) followed by Aspartame (32%), 13% of them are completely not aware of the type of artificial sweetener that they consumed. About 36.7% of the subjects belonged to pre-obese category with BMI 25-29.9kg/m2 with women on the upper scale. 57.91% of the respondents started consuming artificial sweeteners in the recent years i.e., between 1to 5 years. 87% of the subjects consumed artificial sweeteners in the form of pellets in tea or coffee as a medium and 51% consumed it to manage blood glucose levels. 51.2% had gastrointestinal side effects. Significant number of the subjects (81.5%) was unaware of the long-term side effects of artificial sweeteners. Conclusions: The study findings highlight the high rate of unawareness amongst the subjects regarding the side effects of long-term consumption of artificial sweeteners. Hence, reading nutrition label on the products, judicious consumption of artificial sweeteners and nutritional education can be helpful in making wise food choices.